2000
DOI: 10.1073/pnas.97.8.4040
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated GAIP is a phosphoprotein and can be phosphorylated by clathrin-coated vesicles

Abstract: GAIP (G ␣ interacting protein) is a member of the RGS (regulators of G protein signaling) family and accelerates the turnover of GTP bound to G␣i, G␣q, and G␣13. There are two pools of GAIP-a soluble and a membrane-anchored pool. The membrane-anchored pool is found on clathrin-coated vesicles (CCVs) and pits in rat liver and AtT-20 pituitary cells. By treatment of a GAIP-enriched rat liver fraction with alkaline phosphatase, we found that membranebound GAIP is phosphorylated. By immunoprecipitation carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…However, in the presence of 30 mM Mn ϩϩ , the phosphorylation of the GST-GGA1 peptide was stimulated strongly, whereas that of the GST-CI-MPR peptide was reduced, resulting in equivalent phosphorylation. This result is similar to the finding that phosphorylation of the G␣-interacting protein by CK2 is Mn ϩϩ -dependent (16).…”
Section: Binding Of the Gga1 Internal Ac-lm Motif To The Vhs Domain Dsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in the presence of 30 mM Mn ϩϩ , the phosphorylation of the GST-GGA1 peptide was stimulated strongly, whereas that of the GST-CI-MPR peptide was reduced, resulting in equivalent phosphorylation. This result is similar to the finding that phosphorylation of the G␣-interacting protein by CK2 is Mn ϩϩ -dependent (16).…”
Section: Binding Of the Gga1 Internal Ac-lm Motif To The Vhs Domain Dsupporting
confidence: 90%
“…Substitution of an acidic residue at the third position downstream of the serine in GGA2 allowed the molecule to be phosphorylated by CK2. Although the actual kinase that phosphorylates GGA1 and GGA3 in cells has yet to be identified, it should be noted that a CK2-type enzyme has been shown to be associated with clathrin-coated vesicles (16,(21)(22)(23)(24). In preliminary experiments, we found that an activity associated with purified clathrin-coated vesicles phosphorylates the GGA1 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…This is substituted by Ser179 in RGSZ1, Ser150 in RGSZ2, and Ser156 in GAIP (Tesmer et al, 1997;Posner et al, 1999). Moreover, the membrane-bound pool of GAIP is phosphorylated in the N-terminus (Fischer et al, 2000), and at Ser151 that lies inside the RGS domain (Ogier-Denis et al, 2000). The RGS-Rz subfamily binds with the dileucine-rich region of GIPN (GAIP interacting protein N terminus), a putative E3 ubiquitin ligase that links the RGS-Rz proteins with Ga degradation (Fischer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The separated proteins were then transferred to 0.2 mm polyvinylidene difluoride membranes (Bio-Rad). Polyclonal anti-GAIP, -RGSZ1, -GIPC, -Gai2, and -Gaz were diluted typically 1 : 1000 in TBS-0.05% Tween 20 (TTBS) and incubated with the transfer membranes at 61C for 24 h. The anti-GAIP N terminus (1-79) and the 4507 (GAIP 23-217) antibodies, generously provided by T Fischer (De Vries et al, 1998a;Fischer et al, 2000), the RGSZ1 antibody, the Gai2 and the Gaz antibodies Garzón et al, 1997b) were detected with a goat anti-rabbit IgG (H þ L) horseradish peroxidaseconjugate antiserum (BioRad,. While GIPC (Santa Cruz Biotech., Inc, sc-9650) antibody was detected with a donkey anti-goat IgG horseradish peroxidaseconjugate antiserum (sc-2020).…”
Section: Expression Of Rgsz1mentioning
confidence: 99%